The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1161/circimaging.113.000982
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Left Ventricular Global Longitudinal Strain and Adverse Left Ventricular Dilatation After ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Myocardial infarct size is a major determinant of left ventricular (LV) remodeling after ST-segment-elevation myocardial infarction. We evaluated whether LV global longitudinal strain (GLS), proposed as a novel marker of infarct size, is associated with 3-and 6-month LV dilatation after ST-segment-elevation myocardial infarction. Methods and Results-In the first ST-segment-elevation myocardial infarction patients treated with primary percutaneous coronary intervention, baseline LVGLS was measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 39 publications
2
41
0
7
Order By: Relevance
“…10 Previous studies assessing the relationship between longitudinal strain and BMI in populations without overt cardiovascular disease have found significantly reduced strain in obese compared with normal weight subjects and significant correlations between BMI and strain after adjustment for other risk factors. 8,23 In the present study, although normal and overweight patients showed significantly impaired LV GLS early after STEMI at a value (−15.0±4.2%) consistent with previous studies in this population, 13 obese patients had a significantly further impaired level of LV systolic dysfunction (−13.7±3.8%). Notably, this difference between BMI groups is greater than mean intra-and interobserver variability differences as previously published for our institution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 Previous studies assessing the relationship between longitudinal strain and BMI in populations without overt cardiovascular disease have found significantly reduced strain in obese compared with normal weight subjects and significant correlations between BMI and strain after adjustment for other risk factors. 8,23 In the present study, although normal and overweight patients showed significantly impaired LV GLS early after STEMI at a value (−15.0±4.2%) consistent with previous studies in this population, 13 obese patients had a significantly further impaired level of LV systolic dysfunction (−13.7±3.8%). Notably, this difference between BMI groups is greater than mean intra-and interobserver variability differences as previously published for our institution.…”
Section: Discussionsupporting
confidence: 91%
“…13 All patients were treated according to the institutional STEMI (MISSION!) protocol which is based on recent guidelines 14 and provides a clinical framework for optimal guideline-based medical therapy and standardized outpatient follow-up.…”
Section: Patientsmentioning
confidence: 99%
“…Interestingly, despite similar mild reduction in LV ejection fraction (46±9%, 48±9%, and 47±9%, respectively) in normal/underweight (BMI<25 kg/m 2 ) STEMI patients, they found that LV global longitudinal strain (GLS) was also reduced in normal and overweight patients (−15.0±4.2), 3 but obese patients had a significantly more impaired LV GLS (−13.7±3.8%). This was observed despite similar infarct characteristics across the BMI groups.…”
Section: See Article By Joyce Et Almentioning
confidence: 91%
“…ВПО Сибирский медицинский университет Минздрава России, Томск; 3 Нацио нальный исследовательский Томский государственный университет, Томск, Россия.…”
unclassified
“…Преи-муществом является возможность количественной оценки систолической и диастолической функции в полуавтоматическом режиме [1]. Высокая межопе-раторская воспроизводимость новой технологии, простота использования, способствовали её скорей-шему внедрению в клиническую практику [2,3].…”
unclassified